Evaluation of Acute Toxicity of Copper Sulphate in Different Tissues of Euphlyctis Cyanophlyctis - Kour, Preetpal; Tripathi, N.K; Poonam (Journal of Asian Scientific Research, 2014)
Copper sulphate, CuSO4.5H2O (Fine Chemical, India), Purity (99%) and CAS No. 7758-98-7, a broad-spectrum inorganic pesticide, has many-fold uses as fungicide, molluscicide and weedicide. The adult Indian skittering frog, Euphlyctis cyanophlyctis was treated In vivo with different sublethal concentrations of CuSO4 (3.5, 5.0, 6.5 and 8.0mg/kg) after calculating the LC50 value which was found to be 10mg/kg. Each dose was injected intraperitoneally once in the treatment period for 24, 48, 72 and 96hrs to study its potential toxic effect using micronucleus test. It was observed that copper sulphate induced a significant increase in frequency of micronuclei at different concentrations in frog for 24, 48, 72 and 96hrs when compared with the control. The results lead us to the conclusion that there is a dose-effect relationship in the induction in the frequencies of MN in different somatic tissues of the frog due to its genotoxic and cytotoxic properties.